Implementation of Numbered Heads Together (NHT) Learning Model to Improve Student Learning Outcomes on Asmaul Husna Material in Grade IV SDN 101953 Pantai Cermin - Sartika, Henny; Rizal, Khairul; Sinaga, Saputra (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to examine the implementation of the Numbered Heads Together (NHT) learning model in improving students’ learning outcomes in Islamic Religious Education subject on Asmaul Husna material for Grade IV students at SDN 101953 Pantai Cermin. The research method employed was classroom action research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects of this research were 25 fourth-grade students. The instruments used included learning outcome tests, student activity observation sheets, and teacher observation sheets. The findings revealed that the application of the NHT learning model significantly improved students’ learning outcomes, as indicated by the increase in average scores across the cycles and the enhancement of student engagement during the learning process. Therefore, it can be concluded that the NHT learning model is effective in improving learning outcomes in Islamic Religious Education, particularly in the Asmaul Husna material.